Foundations of Intervention Research in Instrumental Practice - Hatfield, Johannes L.; Lemyre, Pierre-Nicolas (Frontiers in Psychology, 2016)
The goals of the present study are to evaluate, implement, and adapt psychological skills used in the realm of sports into music performance. This research project also aims to build foundations on how to implement future interventions to guide music students on how to optimize practice toward performance. A two-month psychological skills intervention was provided to two students from the national music academy’s bachelor program in music performance to better understand how to adapt and construct psychological skills training programs for performing music students. The program evaluated multiple intervention tools including the use of questionnaires, performance profiling, iPads, electronic practice logs, recording the perceived value of individual and combined work, as well as the effectiveness of different communication forms. Perceived effects of the intervention were collected through semi-structured interviews, observations, and logs.